Cell-free plasma DNA and purine nucleotide degradation markers following weightlifting exercise - Atamaniuk, J.; Vidotto, C.; Kinzlbauer, M.; Bachl, N.; Tiran, B.; Tschan, H. (European Journal of Applied Physiology, 2010)
The present study aimed to investigate the acute effects of a single bout of high-intensive strength training on the production of cell-free plasma DNA (cf-DNA), as well as on the degradation of purine nucleotides as assessed by the concentration of xanthine (XA) and hypoxanthine (HX) in urine and serum. Twelve trained weightlifters performed six sets of six lifting exercises with 90-95% of the one repetition maximum. Blood samples and urine were obtained 1 h before training, immediately after finishing the exercise session and following 2 h of recovery. Cf-DNA, HX, and XA (in serum) significantly increased (P < 0.05-P < 0.001) immediately after heavy lifting exercise when compared with baseline levels, and significantly decreased (P < 0.05-P < 0.001) after 2 h of recovery. These results indicate that, cf-DNA and oxypurines might be relevant biomarkers for cellular damage, mechanical, energetic, and/or ischemic stress in context with exercise.